Is Herd Behavior Still Persistent in the Saudi Stock Market?This paper inspects the prevalence of Herd Behavior in the Saudi Stock Exchange, using the model suggested by (Bhaduri & Mahapatra, 2013) which regresses the absolute difference between average m - Arabi, Khalafalla Ahmed Mohamed; Abdelmageed, Hemeda Mohamed (Archives of Business Research, 2022)
This paper inspects the prevalence of Herd Behavior in the Saudi Stock Exchange, using the model suggested by (Bhaduri & Mahapatra, 2013) which regresses the absolute difference between average market returns and median, expecting positive effect by absolute market returns and negative one by nonlinear squared market returns. Daily data from January 1, 2007, to December 31, 2020, was analyzed using Ordinary Least Squares, two Censored Regressions (TOBIT), and switching regression. The constant and absolute market returns are both positive, while the nonlinear quadratic term is negative, produced by all estimation methodologies, which confirm model hypothesis. There were two market conditions, and two regimes produced by both censored, and switched regression. The nonlinear coefficient of growing prices is three times that of declining prices, meaning that venture capitalists are more likely to herd during rising market returns than during dropping market returns, according to the censored regression.